Analisis Perhitungan Harga Pokok Pesanan Dalam Menentukan Harga Jual Di Sumber Katon 2, Seputih Surabaya - Marlena Sari , Devi Ayu; Nusantoro, Jawoto; Febri Darmayanti, Elmira (Universitas Muhammadiyah Metro, 2025)
The primary objective of this study is to evaluate the effectiveness of the company's method for determining product selling prices, focusing on identifying and analyzing costs involved in the production process. The methodology employed involved data collection through interviews and direct observation of the company's production process. The analysis included the costs of raw materials, labor, and overhead, as well as how these costs impact the job order cost. The findings revealed that the current job order cost calculation is not entirely accurate, resulting in suboptimal selling prices. This study recommends improvements in the production costing and pricing system, including the use of more systematic calculation methods and the consideration of market factors and profit margins. By implementing these recommendations, the company is expected to be able to set more competitive selling prices and increase its profitability.